From Curative policy to preventive efforts: the role of physicians and corporate management in health maintenance for plantation workers at the Senembah plantation company, 1871-1940 - Affandi, Kiki Maulana; Agustono, Budi; Junaidi; Rasyidin, Muhammad (Medicina Historica, 2024)
Since the late 19th century, the East Sumatran region transformed into Sumatra’s plantation belt, marked by the rise of multinational companies cultivating export commodities such as tobacco, rubber, coconut, and tea. The growth of the plantation industry required a significant labor force, leading to various challenges, including health issues. Harsh working conditions and the exploitation of labor on plantations contributed to the spread of epidemics and tropical diseases, resulting in high mortality rates among workers. This study aims to explore the diverse health issues faced by plantation workers and the efforts made by companies to address them. This historical analysis employs a historical method comprising heuristics, source criticism, interpretation, and historiography. The findings reveal that the Senembah Plantation Company had a particular focus on the health maintenance of its plantation workers. Key actors involved in health maintenance included corporate management, plantation doctors, and the plantation workers themselves. Health maintenance on the plantations was also supported by the Koelie Ordonnantie regulation, which mandated worker treatment in clinics or hospitals. In addition, the company played a role in providing healthcare facilities, such as hospitals and clinics, and participated in the establishment of the Medan Pathology Laboratory in 1906. The company also implemented ongoing efforts to maintain cleanliness and improve plantation sanitation to prevent the spread of tropical diseases.